Impact of diet variation on growth performance, feeding efficiency, health condition and water quality of juvenile short-finned eel (Anguilla bicolor) - Annisa Apriliani Wahyudia; Ching Fui Fui @ Faihana Ching Abdullah; Shigeharu Senoo (Penerbit UTM Press, 2025)
This study aimed to assess the effects of three different types of feed on the growth and feeding performance, water quality and health condition of short-finned eel (Anguilla bicolor) juvenile. This experiment was conducted for 31 days and involved a total of 180 fish with initials of body weight of 202.89±3.80 g and total length of 44.33±0.6 cm. The fish were divided into three groups , with each group were fed with different types of diets: 1) Japfa dough feed (JDF), 2) dough feed made of from grinded marine pellet (GDF) and 3) pelleted feed (PF). Each treatment was prepared in triplicate. The findings revealed that the pellet-type feed (PF) significantly improved the overall growth performance including survival rate (100.00%) and specific growth rate (3.176±1.08 %/day) with excellent feeding performance recorded with lower feed conversion ratio (2.15±0.9) and high protein efficiency ratio (1.15±0.45). Histological examination of the intestine and liver showed no notable differences in condition of fish in all treatments. In conclusion, this study demonstrated that PF is an effective feed and beneficial for improving growth and feeding performance while maintaining health condition of short-finned eel juveniles hence it suggests the potential for developing a promising feed in the future for eel aquaculture industry.